Franchising in Malaysia: issues and research agenda / Khairol Anuar Ishak. - Ishak., Khairol Anuar (2010)
The franchising concept has become a dominant method inter firm (business-to-business) in the distribution of products and services throughout the local and global market to their target end customer. Franchising is also known as a strategic alliance which relatively enduring inter-firm cooperative arrangement between franchisor and franchisee. Franchising has shown the substantial growth and significant success in most of the developed countries, especially in Western countries. In Malaysia, franchising industries has grown steadily during the past decade through intensively franchise development programme conducted by government agency such as Perbadanan Nasional Berhad (PNS). Nevertheless, there is a still lack of study related the franchising in Malaysia, particularly in franchise business survival. Thus, this paper will be explored the issues in franchising and proposed the conceptual framework for effective franchise business model. The framework developed in this paper will provide a guide to the factors that may affect franchise firm’s performance.